INTEGRATING STEM AND PROJECT-BASED DIGITAL WORKSHEETS TO FOSTER 21ST-CENTURY STUDENT CHARACTERS - Budiarti, Retni S; Johari, Asni; Rusdi, Muhammad; Anggereini, Evita (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the effectiveness of STEM–Project-Based Learning (PjBL) integrated E-Student Worksheets in cultivating character development specifically curiosity and creative thinking among biology education students. Using a quasi-experimental post-test-only control group design, the research involved 50 participants equally divided into experimental and control groups. The experimental group engaged with STEM–PjBL-based E-Worksheets, while the control group used conventional worksheets. Statistical analyses, including tests of normality, homogeneity, and independent t-tests, revealed significant differences between the two groups. Students in the experimental class achieved markedly higher levels of curiosity (M = 83.01; p = 0.001) and creative thinking (M = 79.39; p = 0.003) than their counterparts, demonstrating that the integration of STEM and PjBL within digital worksheets not only increases engagement but also fosters deeper character formation by strengthening inquisitiveness, originality, and problem-solving abilities. The study provides evidence that technology-enhanced project-based learning environments can function as catalytic spaces for nurturing essential 21st-century competencies. The novelty of this research lies in its synthesis of STEM, PjBL, and character education within a single digital learning device an integration rarely explored in higher education. By embedding character attributes directly into project workflows, the E-Worksheets move beyond content delivery toward the cultivation of intellectual dispositions. This study contributes a practical framework for designing character-oriented digital learning tools, offering implications for lecturers, curriculum developers, and instructional technologists seeking to promote holistic student development through innovative, technology-supported pedagogical models.